Investigation of Science Terminology for Grade IV Elementary School Students with Hearing Impairments: A First Step Towards Inclusive Science Education - Suparmi, Made; Putu Nanci Riastini; Dewa Gede Firstia Wirabrata (Universitas Pendidikan Ganesha, 2024)
Science learning in elementary schools is not equal for the deaf, especially in inclusive schools because there are many science terminologies that do not have sign language. This causes deaf students to have difficulty understanding science terminology, and abstract concepts that are conveyed verbally in the classroom. This study aims to investigate science terminologies that appear in science material for grade IV elementary school and describe the percentage of the appearance of science terminologies in all science material for grade IV elementary school. This type of research is descriptive research. The subjects of this study used 120 sources of science material for grade IV elementary school. Data collection in this study used document study and structured observation methods. The data analysis technique used the corpus analysis method through Voyant Tools. The results of this study indicate that the terminologies that often appear in science material for grade IV elementary school are 506 terms (338 words and 168 phrases). These terminologies include the words